WAR TERRORS AND TRAUMA: PSYCHOANALYTICAL STUDY OF RAMAYANA REINTERPRETED IN SCION OF IKSHVAKU OF AMISH TRIPATHI - Nair, Aswathy U; K., Balakrishnan (International Journal of Research -GRANTHAALAYAH, 2025)
War has always existed as a major aspect of human history leaving behind everlasting impacts across the world including in shaping cultures, societies and as well as individuals. The questions related to the cause of war and its impacts, including the long term economic, social and cultural consequences keep on increasing but the psychological complexities remain poorly understood such as traumatic memories, behavioural changes etc. Trauma is a deeply troubling and destructive side of human psyche that leaves non-physical wounds which will be externally invisible but internally can cause a long-lasting damaging impact such as even disorders like depression, anxiety etc which needs to be treated at the earliest stage for recovery and healing. The paper delves into Amish Tripathi’s reimagining of the Ramayana in Scion of Ikshvaku through psychoanalytical perspective to understand the human psyche in relation to war and trauma as this modern retelling of the ancient Indian epic convey timeless significance, universal themes and motifs. This is Amish Tripathi’s first book in Ramchandra series, set in a mythical world that blends history and fantasy as it shares the story of Prince Ram who navigates through the challenges of duty, leadership and complexities of war within and with the external world.